2018
DOI: 10.7897/2230-8407.097135
|View full text |Cite
|
Sign up to set email alerts
|

Tropane Alkaloids Production From Callus Culture of Atropa Belladonna L. As Affected by Elicitors and Precursor Feeding

Abstract: Atropa belladonna L is most important commercial source of pharmaceutical tropane alkaloids. Initiation of callus culture on MS solid media with different concentrations of growth regulators as BA and 2,4 D from different explants shows that 2,4-D only at 1.0mg/L and 2.0mg/l gave the highest callus formation score after 21 days. The highest concentration of atropine (376.62 µg/g DW) and scopolamine (103.16 µg/g DW) were obtained from leaf callus on MS medium supplemented with 2,4 D at 0.5 mg/L after 28 days. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…[12] indicated that cultivation of Hyoscyamus reticulatus L. shoots from tissue culture on MS medium with half salt concentration prepared with 0.2 mg.l -1 IBA produced 3.12 root/shoot after 4 weeks of cultivation. [13] were able to obtain the highest percentage of callus induction (88.6%) by cultivating the leaf of Hyoscyamus aureus L. on MS medium prepared with 1.0 mg.l -1 2,4-D interfering with 0.5 mg.l -1 Kin. the weight of the callus reached 1.0 g after 60 days of planting.…”
Section: Introductionmentioning
confidence: 99%
“…[12] indicated that cultivation of Hyoscyamus reticulatus L. shoots from tissue culture on MS medium with half salt concentration prepared with 0.2 mg.l -1 IBA produced 3.12 root/shoot after 4 weeks of cultivation. [13] were able to obtain the highest percentage of callus induction (88.6%) by cultivating the leaf of Hyoscyamus aureus L. on MS medium prepared with 1.0 mg.l -1 2,4-D interfering with 0.5 mg.l -1 Kin. the weight of the callus reached 1.0 g after 60 days of planting.…”
Section: Introductionmentioning
confidence: 99%